Perforación vesicular en un paciente mayor de 60 años - Díaz Pi, Oscar; Rodríguez Varela, Reynaldo; Rodríguez Rodríguez, Miguel Enrique; Grenet Albernas, Alejandro; Ferreira da Silva, Isabela Bezerra (GeroInfo-Revista de Gerontología y Geriatría, 2025)
The perforation of the gallbladder is a strange, but potentially fatal complication, of the acute cholecystitis, when is not treated precociously. We have presented a 72-year-old masculine patient for one year with records of digestive dysfunctions, without previous study, arrived in the emergency department to present diffuse abdominal pain and shock. The Ultrasound abdominal sample a sharp cholecystitis. The emergency surgery, appreciating perforation gallbladder, with free bile in the peritoneum, you proceeds to carry out a colecistostomía.